2002
DOI: 10.1021/ja0258733
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Streptavidin to Mammalian Cells:  Clathrin-Mediated Endocytosis Regulated by a Synthetic Ligand

Abstract: The efficient delivery of macromolecules to living cells presents a formidable challenge to the development of effective macromolecular therapeutics and cellular probes. We describe herein a novel synthetic ligand termed "Streptaphage" that enables efficient cellular uptake of the bacterial protein streptavidin by promoting noncovalent interactions with cholesterol and sphingolipid-rich lipid raft subdomains of cellular plasma membranes. The Streptaphage ligand comprises an N-alkyl derivative of 3 beta-cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 80 publications
3
45
0
Order By: Relevance
“…For example, streptavidin, a protein purified from the bacterium Streptomyces avidinii, shows anticancer activity. 100 However, it cannot penetrate the cells because of its large molecular weight (~60 kDa). Shi Kam et al 101 conjugated streptavidin to an SWCNT-biotin transporter to internalize streptavidin into promyelocytic leukemia (HL60) cells and human T-cells (Jurkat) through the endocytosis pathway (Figure 4).…”
Section: Cnts As Carriers Of Proteins and Immunoactive Componentsmentioning
confidence: 99%
“…For example, streptavidin, a protein purified from the bacterium Streptomyces avidinii, shows anticancer activity. 100 However, it cannot penetrate the cells because of its large molecular weight (~60 kDa). Shi Kam et al 101 conjugated streptavidin to an SWCNT-biotin transporter to internalize streptavidin into promyelocytic leukemia (HL60) cells and human T-cells (Jurkat) through the endocytosis pathway (Figure 4).…”
Section: Cnts As Carriers Of Proteins and Immunoactive Componentsmentioning
confidence: 99%
“…In another study, CNTs cationically functionalized with polyethylene imines have been shown capable of complexing with siRNA and generating a silencing activity of up to 30% and cytotoxicity of up to 60% [44]. Streptavidin is a protein that has anticancer activity [45]; however, due to its very large molecular weight (approximately 60,000 Da), it does not penetrate through cells. Kam and coworkers [12] have used a conjugate of streptavidin with SWNTs-biotin, which resulted in internalization of the protein into model cancer cells by adsorption-mediated endocytosis.…”
Section: Cnts As Carriers Of Immunoactive Compounds Proteinsmentioning
confidence: 99%
“…Avidin drugs that bind to biotinylated vectors are being used to promote delivery across the blood-brain barrier (6,30,41), while antitumor toxins or imaging agents coupled to streptavidin are being delivered with biotinylated antibodies (17,37). Biotinylation has also been shown to promote the delivery of polyethylene glycol-camptothecin conjugates into human ovarian carcinoma cells (24) and increase the cellular uptake of polyethylene glycol-TAT nonapeptide conjugates into human Caco and CHO cells (38).…”
Section: Vol 71 2005 Biotinylation Facilitates the Uptake Of Large mentioning
confidence: 99%